MENCARI VALIDITAS ANALISIS METODE MATERIAL BALANCE TERHADAP METODE SIMULASI RESERVOIR PADA LAPANGAN MINYAK RINGAN DENGAN SKENARIO GAS REINJECTION. - Lana Mahendra, Made
Gas reinjection is one of the reservoir production management methods which commonly used in the petroleum industry in order raising the recovery of oil/condensate reservoir and maintaining reservoir pressure. There are two methods that are used in this study, there are material balance method and reservoir simulation method. Material balance method is used to see the effect of gas injected to recovery of oil and gas by take an advantage in simplicity of the model using black oil model. Reservoir simulation method is using compositional model to see in detail about the effect of gas injected to fluid behavior in reservoir and the recovery of oil and gas. This study purposes to determine how much difference of analysis result from material balance method compared to reservoir simulation in predicting reservoir performance with gas reinjection scenario. It can be expected from this study when the material balance method will generate same or similar results as reservoir simulation method, thus we can save more time and cost to model the reservoir performance. This study conducted in field located in Natuna Sea. This field has three productive zones which consist of two light oil zones and one dry gas zone. Gas reinjection scenario has been conducted in one light oil reservoir and will be modeled using both material balance and reservoir simulation to predict reservoir performance for about 15 years and will be compared the effect of gas injection to reservoir performance from reservoir simulation and material balance. In this study, it can be conclude that material balance method and reservoir simulation method will show same or get near to each other prediction result at some conditions; plenty/long production history data, not too high gas injection rate, low reservoir heterogenity and low reservoir pressure.